2012
DOI: 10.1523/jneurosci.4765-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin-GPR54 Signaling in Mouse NO-Synthesizing Neurons Participates in the Hypothalamic Control of Ovulation

Abstract: Reproduction is controlled in the brain by a neural network that drives the secretion of gonadotropin-releasing hormone (GnRH).Various permissive homeostatic signals must be integrated to achieve ovulation in mammals. However, the neural events controlling the timely activation of GnRH neurons are not completely understood. Here we show that kisspeptin, a potent activator of GnRH neuronal activity, directly communicates with neurons that synthesize the gaseous transmitter nitric oxide (NO) in the preoptic regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
103
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(118 citation statements)
references
References 78 publications
(103 reference statements)
13
103
1
1
Order By: Relevance
“…Pubertal activation was never detected in Nos1 -/-Lep ob/ob mice, while the first estrous cycle occurred 13 days from the start of the leptin regimen in Nos1 +/+ Lep ob/ob littermates and remained variable thereafter, typically lasting 4 to 5 days (Figure 4, B and E). The Nos1 -/-single-mutant (Nos1 -/-Lep +/+ ) mice demonstrated an ovulatory pattern, as reported in other studies (15,30), suggesting that the lack of nNOS alone is not responsible for the continued infertility of Nos1 -/-Lep ob/ob mice.…”
Section: Figuresupporting
confidence: 76%
See 3 more Smart Citations
“…Pubertal activation was never detected in Nos1 -/-Lep ob/ob mice, while the first estrous cycle occurred 13 days from the start of the leptin regimen in Nos1 +/+ Lep ob/ob littermates and remained variable thereafter, typically lasting 4 to 5 days (Figure 4, B and E). The Nos1 -/-single-mutant (Nos1 -/-Lep +/+ ) mice demonstrated an ovulatory pattern, as reported in other studies (15,30), suggesting that the lack of nNOS alone is not responsible for the continued infertility of Nos1 -/-Lep ob/ob mice.…”
Section: Figuresupporting
confidence: 76%
“…The preoptic region of the hypothalamus is one of the major sites for the expression of nNOS within the basal forebrain (36,37), in which the release of NO has been linked to the secretion of GnRH and stimulation of the preovulatory surge of GnRH/LH (15, 38-40). The importance for nNOS activity in reproductive functioning is highlighted by the detrimental effects on fertility in nNOS-deficient female mice, ranging from sporadic ovulation and blunted preovulatory LH secretion to complete hypothalamic hypogonadism (15,30,41). Intriguingly, nNOS neurons within the preoptic region have been shown to be key integrators of neural signals involved in reproduction (15,39,42,43), in which the local activation of nNOS and subsequent production of NO exert a tonic inhibitory tone on surrounding GnRH neurons (14,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, an increasing body of evidence supports the idea that GnRH neurons in mammals are regulated by distinct neuronal networks and interactions via specific cell-cell signalling molecules, which may be affected by the modulatory influence of gonadal steroids (Bellefontaine et al, 2011;Prevot, 2002;Radovick et al, 2012). In mice, nitric oxide (NO) is probably involved in mediating the estrogenic positive feedback of Kiss1 onto GnRH neurons (Hanchate et al, 2012). Recent data in sea bass have shown that kissr2 (also referred to as gpr54-2b or kissr3) is expressed in NO-positive cells (Escobar et al, 2013b), although its potential interaction with kisspeptins and the mediation of steroid feedback is still unknown.…”
Section: Discussionmentioning
confidence: 99%